ACL Repair of Femoral Osseous Avulsion in a 13-Year-Old Using Suture Pullout Technique - Andrew Moore BS; Jess Rames BS; Kathy McGurk MD; Harris Slone MD (SAGE Publishing, 2021)
Background: The incidence of pediatric anterior cruciate ligament (ACL) injuries has been increasing over the past 20 years, with the majority comprised of mid substance tears or tibial eminence avulsion fractures. Pediatric femoral sided osseous avulsion is rarely reported in orthopedic literature and specific surgical indications and contraindications, as well as recommended surgical techniques and postoperative rehabilitation protocols, are underdefined. Indications: The surgical indications for femoral-sided repair of ACL osseous avulsion includes a displaced osseous fragment and ligamentous laxity on physical examination. There was no concomitant midsubstance tear necessitating reconstruction. Technique Description: Two sutures piercing the proximal ligamentous bony junction of the ACL were fed through 2.4-mm transphyseal tunnels and secured with cortical button and backup fixation with a 3.9-mm swivel lock anchor in the proximal lateral femoral metaphysis. The patient was immobilized in a hinged-knee brace locked in extension during ambulation and limited to 90 degrees of flexion while nonweightbearing for the first 6 weeks after surgery. Standard ACL protocol was followed thereafter. Results: Successful fixation and restoration of ligamentous tension and impingement-free range of motion were achieved without complication. There was stable Lachman, negative pivot shift, 125 degrees of knee flexion, and evidence of early healing at 3 months follow-up. Discussion/Conclusion: This report demonstrates successful reduction and fixation of proximal bony avulsion of the ACL. Although this patient exhibits stable physical examination and undisturbed growth at early follow-up, more research is required to establish treatment and rehabilitation guidelines for this rare injury.